2019
DOI: 10.1101/2019.12.16.878298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene expression data support the hypothesis that Isoetes rootlets are true roots and not modified leaves

Abstract: Rhizomorphic lycopsids are the land plant group that includes the first giant trees to grow on Earth and extant species in the genus Isoetes. Two mutually exclusive hypotheses account for the evolution of terminal rooting axes called rootlets among the rhizomorphic lycopsids. One hypothesis states that rootlets are true roots, like roots in other lycopsids. The other states that rootlets are modified leaves. Here we test predictions of each hypothesis by investigating gene expression in the leaves and rootlets… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…An annotated S. moellendorffii genome was published by Banks et al, (2011), and there are RNASeq and DNASeq datasets from S. kraussiana (Table 1; Ge et al, 2016). Several lycophyte transcriptomes such Selaginella martensii and Isoëtes echinospora have recently been published (Hetherington, Emms, Kelly, & Dolan, 2019; James et al, 2017; Leebens‐Mack, 2019) and lycophyte transcriptomes from Isoëtes drummondii and Phylloglossum drummondii are also available on request (Table 1; Dixon, Harrison, Hetherington, Mylne, & Zhang, 2016). Such genomic and transcriptomic data are important for analyses of gene copy number and the identification of developmental gene orthologs and will facilitate future evo‐devo studies by providing templates for primer design.…”
Section: Genomic and Genetic Resources For Lycophytesmentioning
confidence: 99%
See 4 more Smart Citations
“…An annotated S. moellendorffii genome was published by Banks et al, (2011), and there are RNASeq and DNASeq datasets from S. kraussiana (Table 1; Ge et al, 2016). Several lycophyte transcriptomes such Selaginella martensii and Isoëtes echinospora have recently been published (Hetherington, Emms, Kelly, & Dolan, 2019; James et al, 2017; Leebens‐Mack, 2019) and lycophyte transcriptomes from Isoëtes drummondii and Phylloglossum drummondii are also available on request (Table 1; Dixon, Harrison, Hetherington, Mylne, & Zhang, 2016). Such genomic and transcriptomic data are important for analyses of gene copy number and the identification of developmental gene orthologs and will facilitate future evo‐devo studies by providing templates for primer design.…”
Section: Genomic and Genetic Resources For Lycophytesmentioning
confidence: 99%
“…Genetic studies would determine if lycophyte roots are homologous, or if pre‐existing organs such as leaves acquired root‐like characteristics and associated genetic signatures convergently (Hetherington & Dolan, 2017). A transcriptomic approach recently showed that the short rootlets of Isoëtes echinospora are more transcriptionally similar to Selaginella and Arabidopsis roots than leaves, addressing a longstanding question about the identity of rhizomorphic lycopsid rootlets (Hetherington et al, 2019). It will be important to identify genetic similarities between other root types and the organs on which roots are borne to identify conservation, convergence, and divergence in root evolution.…”
Section: Analyses Of Gene Functions In Trait Evolutionmentioning
confidence: 99%
See 3 more Smart Citations